Upaya Mengatasi Kecanduan Anak Terhadap Gawai (Gadget) Melalui Model Komunikasi Interaktif Orang Tua dan Anak Berdasar Al-Quran - Fera Andriani Djakfar Musthafa (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
In the modern era, the use of devices is already very widespread, even among children. Devices enable children from accessing information easily and quickly. Otherwise, devices also offer other things, such as games and entertainment that can lead to addiction. Meanwhile, the communication between parents and children often have problems that affect loosening the relationship between them. The purposes of this article are to determine the negative impact of device addiction to the children, how are the forms of interactive communication between parents and children exemplified by the Quran, and how can the interactive communication be an effort to save children from device addiction. The negative impacts of device addiction are such as decreased concentration, lack of emotional control, and health disorder. Interactive communication between parents and children in the Quran such as the story of Prophet Abraham who discussed and listened to the opinion of Ismael, Prophet Zakariya who used to be critical and inquisitive about unusual phenomena experienced by Maryam, Lukman Al Hakim showed a good way in advising the child, and Nuh gave an example of how to reprimand Kan'an. With those kinds of interactive communication models, hopefully parents can find the right way to communicate and could successfully counseled the children to release them from device addiction.Keywords: Gadget, mobile phone, interactive communication model